Gender, Costume, Textile, Technique : Women, Clothing, Cultural Representation and Modern Japan - Hartley, Barbara, (Asian Studies E-Books Online, Collection 2025., 2025)
This book, a unique contribution to the field of kimono and Japan-related clothing studies, challenges uncritical readings of clothing from the lives of Japanese women and cultural representations of women wearing these clothes. Chapters ground understandings of clothing, including kimono, in the lived experience of different groups of women in modern Japan. Also discussing cosplay outside Japan, the collection argues that items worn by women are produced and consumed in a gendered and highly politicised socio-historical environment. Examining, for example, women's recent renewed enthusiasm for kimono, in addition to representations of monpe , kimono and other attire in film and narrative, the book includes three new translations of clothing commentary by women writers from Japan. Contributors are: Tomoko Aoyama, Yasuko Claremont, Sheila Cliffe, Barbara Hartley, Helen Kilpatrick, Emerald King, Machiko Iwahashi, Komashaku Kimi, Rio Otomo, Sata Ineko, Jennifer Scott, and Shirasu Masako.